2018
DOI: 10.1038/sdata.2018.91
|View full text |Cite|
|
Sign up to set email alerts
|

HYSOGs250m, global gridded hydrologic soil groups for curve-number-based runoff modeling

Abstract: Hydrologic soil groups (HSGs) are a fundamental component of the USDA curve-number (CN) method for estimation of rainfall runoff; yet these data are not readily available in a format or spatial-resolution suitable for regional- and global-scale modeling applications. We developed a globally consistent, gridded dataset defining HSGs from soil texture, bedrock depth, and groundwater. The resulting data product—HYSOGs250m—represents runoff potential at 250 m spatial resolution. Our analysis indicates that the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 16 publications
0
94
0
2
Order By: Relevance
“…The satellite imaging technique and geographic information system (GIS) were incorporated with the conventional SCS-CN method for studies but no attempt was reported to calibrate the primary SCS-CN rainfall-runoff framework with statistics in recent years. Recently, two groups of researchers developed a globally gridded CN dataset at 250 m spatial resolution [23,24]. However, the 250 m resolution dataset only represents general patterns of soil runoff potential appropriate for regional to global-scale analyses and may not capture the local variance suitable for fine-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…The satellite imaging technique and geographic information system (GIS) were incorporated with the conventional SCS-CN method for studies but no attempt was reported to calibrate the primary SCS-CN rainfall-runoff framework with statistics in recent years. Recently, two groups of researchers developed a globally gridded CN dataset at 250 m spatial resolution [23,24]. However, the 250 m resolution dataset only represents general patterns of soil runoff potential appropriate for regional to global-scale analyses and may not capture the local variance suitable for fine-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…The soil hydrologic group of the studied basin was classified as (HSG-B: moderately low runoff potential where 50-90% sand and 10-20% clay) according to Global Hydrologic Soil Groups. These data are accessed through the Oak Ridge National Laboratory (ORNL DAAC 2017) Distributed Active Archive Center (DAAC) for Curve Number-Based Runoff Modeling by using the Geospatial Data Visualization tool (Ross et al 2018).…”
Section: Estimation Of Surface Runoffmentioning
confidence: 99%
“…According to the classification based on soil texture, seven types of soils are found in the Vishwamitri watershed ( Figure 10) (typically contains more than 90% sand and less than 10% clay), HSG-B has moderately low runoff potential (typically contains between 10 to 20% clay and 50 to 90% sand), HSG-C has moderately high runoff potential (typically contains between 20 to 40% clay and less than 50% sand) and HSG-D has high runoff potential (typically contains more than 40% clay and less than 50% sand) Ross et al (2018). (2014)).…”
Section: Soil Texturementioning
confidence: 99%